DEVELOPMENT OF COMPETENCE QUALITIES IN STUDENTS - Pulatova Nazira Melievna; M.Ergasheva (Scholar Express Journals, 2023)
This article deals with the development of students' competence. The issues of theory and practice of introducing the pedagogical foundations for the development of students' competence are considered. The concept and structure of students' competence are analyzed.
Keywords: technology; social competence; cooperation; behavior